Health education and clinical care of immigrant women with female genital mutilation/cutting who request postpartum reinfibulation. Issue 1 (October 2016) - Abdulcadir, Jasmine; McLaren, Sophie; Boulvain, Michel; Irion, Olivier
Abstract: Objective: To evaluate the percentage of women with female genital mutilation/cutting who request postpartum reinfibulation, and to assess outcomes after specific care and counseling. Methods: A retrospective review was undertaken of consecutive medical files of immigrant women with FGM/C who attended a center in Geneva, Switzerland, between April 1, 2010, and January 8, 2014. The number of postpartum reinfibulation requests and outcomes were assessed. If a patient requests postpartum reinfibulation despite receiving detailed information and counseling, a longer follow‐up is arranged for further counseling. Results: Among 196 women with FGM/C, 8 (4.1%) requested postpartum reinfibulation. All eight were of East African origin, had FGM/C type III, and received a longer and more targeted follow‐up than did those who did not request reinfibulation. After at least 1 year of follow‐up, none of the eight was willing to undergo reinfibulation. One woman who attended the clinic only once during her first pregnancy consulted the emergency ward of the study center 3 years later because of postcoital bleeding following infibulation performed in her home country a few months after her second delivery in Switzerland. Conclusion: Specific care and counseling for women with FGM/C type III can improve the acceptability of defibulation without reinfibulation.